Impact of treatment modality on pelvic floor dysfunction among uterine cancer survivors. Issue 10 (9th June 2022) - Lakomy, David S; Yoder, Alison K; Wu, Juliana; Hernandez, Mike; Ayoola-Adeola, Martins; Jhingran, Anuja; Klopp, Ann; Soliman, Pamela; Peterson, Susan K; Lin, Lilie L
Abstract : Objective: Pelvic floor dysfunction is a common adverse effect of uterine cancer treatment. In this study we compared patient-reported outcomes regarding pelvic floor dysfunction among uterine cancer survivors after hysterectomy and bilateral salpingo-oophorectomy, surgery and brachytherapy, or surgery and external beam radiotherapy with or without brachytherapy versus women who had a hysterectomy for benign indications. Methods: We used the validated 20-item Pelvic Floor Distress Inventory to assess lower urinary distress, colorectal distress, and pelvic organ prolapse dysfunction in each treatment group. Pelvic floor dysfunction-related quality of life in these domains was compared across treatment modalities using the Pelvic Floor Impact Questionnaire-7. Treatment type, body mass index, comorbidities, and number of vaginal births were obtained from medical records. A zero-inflated negative binomial regression model was used to assess the association of treatment regimens and covariates relative to the non-cancer cohort. Results: A total of 309 surveys were analyzed. The median age of the patients at surgery was 58 years (range 20–87) and the median age at survey completion was 66 years (range 34–92). Most participants reported experiencing at least one symptom of pelvic floor dysfunction (76% by Pelvic Floor Distress Inventory-2). The type of treatment had no effect on overall pelvic floor dysfunction on multivariate analysis (all p>0.05). Worse urinary-related symptoms were associated with higher body mass index at surgery (OR 1.41), higher age at time of survey (OR 1.07), and higher numbers of vaginal births (OR 1.43) (all p<0.05). Conclusions: Overall, pelvic floor dysfunction did not significantly vary by treatment modality. Our findings suggest complex interactions among age, body mass index, and parity as to how uterine cancer treatment affects pelvic floor quality of life, which should be considered in the choice of treatment strategy and patient counseling.